Cơ cấu hội đồng quản trị, kỷ luật thị trường có ảnh hưởng đến mức độ công bố thông tin trong báo cáo thường niên? Bằng chứng từ các ngân hàng thương mại Việt Nam - Nguyen Cong , Phuong; Nguyen Thi Ha , My (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
This paper aims to study the extent of disclosure and clarify whether the composition of the board of director and market discipline have an impact on the disclosure in the annual report of Vietnamese listed banks. Based on the positive approach, quantitative research methodology, the study used the disclosure index to measure the level of information disclosure and the regression model to assess the impact of board of composition and market discipline on disclosure in the annual report of 33 commercial banks for a period of three years (2012–2014). The analysis shows that the level of disclosure in the annual report of banks is low; the board of composition and market discipline did not affect the level of disclosure of banks. This result provides implications for measuring these variables in the future.
Keywords: Disclosure; Annual report; Disclosure index; Board of director; Market discipline